Kudzidza nokudzidzisa nhetembo - Magwa, Wiseman (Harare : SAPES Books, 1997)
The learning and teaching of Shona poetry.
Includes bibliographical references (p. [81]).
In Shona.
Keywords: Shona poetry -- History and criticism; Shona poetry -- Study and teaching